A wideband and high‐gain fully metallic lens antenna for terahertz applications. Issue 9 (16th March 2022) - Xiong, Qi; Ye, Jia; Pan, Wei; Yan, Lianshan
Abstract: In this letter, a high‐gain fully metallic lens antenna operating in 110–170 GHz frequency range is designed and fabricated. The antenna is composed of a feeding E‐plane horn, a metallic lens and a flared H‐plane horn. The metallic lens consisting of oblique metal plates and two horn arrays is used to compensate the phase difference in the E‐plane. A prototype is fabricated in aluminium by low‐cost computer numerical control milling technology. Experiments are carried out to verify the design. Measurement results of the prototype show that the proposed antenna can achieve a wide impedance bandwidth of 42.85% across 110–170 GHz with an input reflection coefficient below −10 dB. In addition, the maximum gain is 29.2 dBi at 170 GHz. These performances of the proposed antenna indicate the potential for terahertz applications.